2013
DOI: 10.1007/s11051-013-1607-4
|View full text |Cite
|
Sign up to set email alerts
|

Patchy silica-coated silver nanowires as SERS substrates

Abstract: We report a class of core-shell nanomaterials that can be used as efficient surfaceenhancement Raman scattering (SERS) substrates. The core consists of silver nanowires, prepared through a chemical reduction process, that are used to capture 4-mercaptobenzoic acid (4-MBA), a model analyte. The shell was prepared through a modified Stöber method and consists of patchy or full silica coats. The formation of silica coats was monitored via transmission electron microscopy, UV-visible spectroscopy and phase-analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…SSW were nominally 50 mm 9 10 mm diameter pads while SSC dimensions were 10 cm 9 2 cm. Au NPs were prepared by a citrate reduction approach [8][9][10][11]13,14,16 in the presence of the filter support. Specifically, 1.25 9 10 À4 M Au 3+ was heated to boiling and 1 wt.% sodium citrate solution was added.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…SSW were nominally 50 mm 9 10 mm diameter pads while SSC dimensions were 10 cm 9 2 cm. Au NPs were prepared by a citrate reduction approach [8][9][10][11]13,14,16 in the presence of the filter support. Specifically, 1.25 9 10 À4 M Au 3+ was heated to boiling and 1 wt.% sodium citrate solution was added.…”
Section: Methodsmentioning
confidence: 99%
“…[8][9][10][11]13,14,16,17 It was found that the size and density of the nanoparticles' formation depends on many factors such as the reaction temperature and duration of the process as well as the nature of the solid supports and their surface energy. The desired NP size and loading density were controlled and tailored by careful selection of experimental parameters as previously reported by us.…”
Section: Nanoparticle Preparation and Growth Mechanismmentioning
confidence: 99%
See 3 more Smart Citations